Penanaman Kedisiplinan Pada Anak Usia Dini Melalui Permainan Tradisional Di RA Al Islam Petala Bumi - Aisyah Purnama Sari; Dessy Syofiyanti (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2022)
One of the applications of early childhood education that must be instilled is the value of discipline, because it is during this period that a person's personality begins to be formed. Based on the pre-cycle that the researchers conducted, several student problems at RA Al Islam Petala Bumi were found related to discipline at school, namely: 1). Passive students in the learning process, 2). Students are often not disciplined in following class rules, 3). Students often make noise in class, 4). Students lack concentration in participating in learning, 5). Students do not have the will to work on learning, 6). Students are less interested in the teaching aids provided by the teacher. The impact that occurs from the learning process affects the activeness of students in learning in class, students tend to just be silent and listen to the teacher teaching so that students have no interest in doing the assignments that have been given by the teacher. This research was conducted using a Qualitative Method with a Classroom Action Approach with the Kurt Lewin Model which was carried out in 2 (two) cycles, with the results of the research that there was an increase in student discipline in learning through traditional games at RA Al Islam Petala Bumi Village besides being able to develop Cognitive, Affective and motor children